BODY-ORIENTED DIRECTION IN PSYCHOTHERAPY - Solovjova, Yu.M. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
In the article there is a short description of the main systems of the body-oriented psychotherapy, both known and new. Body-oriented psychotherapy becomes very close to the medicine, having the same subject of research and exerting efforts – the human body. In modern systems, for example, in Bodynamic Analysis, these two sciences practically intersect. Bodily feelings, pain, the structure of the muscular shell become a diagnostics in psychotherapy, and a work with them leads to the healing of many psychosomatic diseases.